2015
DOI: 10.2174/1871527313666141130203245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Depressive Symptoms and Biomarkers in Depression

Abstract: Regular physical exercise/activity has been shown repeatedly to promote positive benefits in cognitive, emotional and motor domains concomitant with reductions in distress and negative affect. It exerts a preventative role in anxiety and depressive states and facilitates psychological well-being in both adolescents and adults. Not least, several meta-analyses attest to improvements brought about by exercise. In the present treatise, the beneficial effects of exercise upon cognitive, executive function and work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 231 publications
4
77
0
1
Order By: Relevance
“…Our results and those of others by no means suggest overlooking the health benefits of exercise or not including physical activity in weight loss or management plans. There is ample evidence that exercise reduces cardiovascular disease and all causes of mortality (Hupin et al, 2015; Stewart, Benatar, & Maddison, 2015) as well as positive benefits in cognitive and emotional domains of health (Archer, Josefsson, & Lindwall, 2014). Our findings may be important to consider only in the context of weight loss, not in the context of overall health.…”
Section: Discussionmentioning
confidence: 99%
“…Our results and those of others by no means suggest overlooking the health benefits of exercise or not including physical activity in weight loss or management plans. There is ample evidence that exercise reduces cardiovascular disease and all causes of mortality (Hupin et al, 2015; Stewart, Benatar, & Maddison, 2015) as well as positive benefits in cognitive and emotional domains of health (Archer, Josefsson, & Lindwall, 2014). Our findings may be important to consider only in the context of weight loss, not in the context of overall health.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that there are differences expressed between those parents with and those without core eatingdisorder psychopathology; those parents presenting eating-disorder psychopathology reported greater perceived feeding responsibility, stronger concerns about their children's weight management and spent more time monitoring the children's intake behavior than those parents not presenting eating-disorder characteristics [23]. The notion concerning the conceptualization and measurement of pathological exercise in association with eating disorder, not least AN, is not novel, not least in its connotations with perfectionism and compulsive behaviour [24]. In a sample of 1,497 adult (608 men, 885 women, 4 other) individuals, it was found that those linked to physical exercise and an accompanying eating disorder, i.e.…”
Section: Editorialmentioning
confidence: 96%
“…This line of research has shown that individuals who adhere to different forms of conscious and planned physical exercise do not only improve their physical health and performance, but also psychological health, well-being, and intellectual performance (Archer and Garcia, 2014; Garcia et al, 2012). Among the elderly, for example, regular physical exercise with sufficient degree of physical effort and energy expenditure, serve as a proactive and prevention buffer against symptoms and biomarkers for several neurodegenerative and psychiatric disorders (Archer, 2012; Archer and Kostrzewa, 2015; Archer and Kostrzewa, 2016; Archer et al, 2014; Garcia and Archer, 2014). …”
Section: Introductionmentioning
confidence: 99%